Prediction of Severe Exacerbations and Mortality in COPD: the Role of Exacerbation History and Inspiratory Capacity/Total Lung Capacity Ratio - Cardoso, J (2018)
BACKGROUND: Severe exacerbations and mortality are major outcomes in COPD, and risk factors for these events are actively searched for. Several predictors of mortality have been identified in COPD. The inspiratory capacity/total lung capacity (IC/TLC) ratio has been shown to be a strong predictor of all cause and respiratory mortality in patients with COPD. The major objectives of this study were to analyze which clinical parameters, including lung volumes, were the best predictors of the 5-year cumulative risk of hospital admissions or death and the 5-year risk of exacerbations, in stable COPD patients. METHODS: This study retrospectively reviewed data from 98 stable COPD patients, consecutively recruited in 2012. Forced expiratory volume in 1 s (FEV1), modified Medical Research Council dyspnea scale, exacerbation history (ExH), Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2011 groups, and lung volumes were reviewed. Five years later, this population was evaluated for cumulative exacerbations, hospital admissions, and mortality. All the population, and GOLD group D separately, were analyzed. RESULTS: The cumulative 5-year combined risk of hospital admission or death was significantly predicted by the ExH and the IC/TLC ratio. Analyzing separately group D, FEV1 was the only predictor of this outcome. The frequency of exacerbations in the previous year was the best predictor of future cumulative 5-year risk of subsequent exacerbations, both for the total population and the GOLD D group. CONCLUSION: ExH and IC/TLC ratio were the best predictors of the most severe outcomes in COPD (admissions or mortality), independently of COPD severity. FEV1 was the only predictor of the cumulative 5-year combined risk of hospital admission or death in the GOLD D group. ExH was the best predictor of 5-year cumulative future risk of exacerbations. Besides FEV1 and ExH, the IC/TLC ratio can be a useful predictor of severe outcomes in COPD.